2022
DOI: 10.3389/fonc.2021.754104
|View full text |Cite
|
Sign up to set email alerts
|

rs62139665 Polymorphism in the Promoter Region of EpCAM Is Associated With Hepatitis C Virus-Related Hepatocellular Carcinoma Risk in Egyptians

Abstract: Hepatocellular carcinoma (HCC) is a universal health problem that is particularly alarming in Egypt. The major risk factor for HCC is hepatitis C virus (HCV) infection which is a main burden in Egypt. The epithelial cell adhesion molecule (EpCAM) is a stem cell marker involved in the tumorigenesis and progression of many malignancies, including HCC. We investigated the association of -935 C/G single nucleotide polymorphism in EpCAM promoter region (rs62139665) with HCC risk, EpCAM expression and overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Several studies have found links between the occurrence of HCC and certain SNPs. [19,20] Genetic variations in lncRNAs have recently received a lot of attention with a significant contribution of lncRNA SNPs to the susceptibility to carcinogenesis due to their profound effects on gene expression. [21] Genetic polymorphisms of H19 were previously linked to the occurrence and development of liver cancer.…”
mentioning
confidence: 99%
“…Several studies have found links between the occurrence of HCC and certain SNPs. [19,20] Genetic variations in lncRNAs have recently received a lot of attention with a significant contribution of lncRNA SNPs to the susceptibility to carcinogenesis due to their profound effects on gene expression. [21] Genetic polymorphisms of H19 were previously linked to the occurrence and development of liver cancer.…”
mentioning
confidence: 99%